1998
DOI: 10.1046/j.1365-2958.1998.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

A negative regulator linking chromosome segregation to developmental transcription in Bacillus subtilis

Abstract: SummaryThe Spo0JA and Spo0JB proteins of Bacillus subtilis are similar to the ParA and ParB plasmid-partitioning proteins, respectively, and mutation of spo0JB prevents the expression of stage II genes of sporulation. This phenotype is a consequence of Spo0JA activity in the absence of Spo0JB, and its basis was unknown. In the studies reported here, Spo0JA was found specifically to dissociate transcription initiation complexes formed in vitro by the phosphorylated sporulation transcription factor Spo0A and RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 51 publications
(60 reference statements)
2
65
0
Order By: Relevance
“…Soj associates with several sporulation promoters in vivo (36) and at least one of these promoters in vitro (4). We tested for the association of Soj with the spo0A promoter region in vivo by using a cross-linking-immunoprecipitation assay (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Soj associates with several sporulation promoters in vivo (36) and at least one of these promoters in vitro (4). We tested for the association of Soj with the spo0A promoter region in vivo by using a cross-linking-immunoprecipitation assay (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…All of these promoters are also activated by Spo0AϳP, but association of Soj with the promoter regions in vivo was independent of spo0A (data not shown). It is possible that Soj interacts with a binding site similar to that for Spo0A, but in vitro experiments have indicated that Soj binding to DNA is complicated and that Soj is not simply recognizing the same sequences as Spo0A (4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations